The people have spoken: abide? A critical view of the EU's dramatic referendum (in)experience. (6th December 2016) - Auer, Andreas
Abstract : 6 December 1992 – 9 February 2014 – 23 June 2016: three national referendums related to the European integration process, the first two in Switzerland, the third in the United Kingdom, with a hardly expected but unmistakably clear anti-European and anti-establishment outcome. The people have spoken, the matter is settled, governments have to abide. So goes the common understanding. In constitutional terms and in the theory of (direct) democracy, however, things may look different.